(untitled) (International Journal of Engineering and Computer Science, 2015)
Grid computing is the collaboration of interconnected computing resources ready to be served for the user’s request for complex and time consuming processes. Task scheduling is one among the thrust research areas of grid computing as it can be viewed as an NP- complete problem. Task scheduling is still complicated as the resources in the grid environment have unique characteristics in nature. Thus, the allocations of resources have limited opportunities in finding out the optimal solution. Over the past decades, many researches have been proposed on heuristics task scheduling algorithms that contributed a substantial impact on the performance of task scheduling. Unfortunately, the algorithms are still lacking in producing cent percent of optimal solution in the allocation of resources to the needy systems. The evaluations of the optimal solution are also found more difficult to prove the efficiency of the algorithms. Therefore, this review is motivated to present the depth study on grid computing environment, existing heuristics scheduling algorithms and their significances. This paper also includes the comparative analysis of the reviewed algorithms using the most dominating parameters.